142k views
16 votes
Help don’t understand

Help don’t understand-example-1

1 Answer

7 votes

Answer:

f(-14) = -6

f(-4) = 6

f(12) = 6

f(0) = -3

negative

Explanation:

f(-14) = -6

This is because when x is -14, y is -6, as seen in the graph

f(-4) = 6

This is because when x is -4, y is 6, as seen in the graph

f(12) = 6

This is because when x is 12, y is 6, as seen in the graph

f(0) = -3

This is because when x is 0, y is -3, as seen in the graph

is f(4) positive or negative?
negative

This is because when x is 4, y is -6, as seen in the graph

User Idmitme
by
6.4k points